IMPLEMENTATION OF VILLAGE INDEX DEVELOPMENT POLICY (A Study in Kutawaringin District, Bandung Regency) - Hidayat Hidayat; Siti Sulastri; Endah Christianingsih (Jurnal Sosial Humaniora, 2021)
This study focuses on the Implementation of Village Index Development Policy in Kutawaringin District, Bandung Regency with a sub-focus of research, namely communication factors, resources, disposition and bureaucratic structure. With the aim of knowing and analyzing the Implementation of Village Index Development Policy. This research uses qualitative research method, with data analysis techniques that include data collection, data reduction, data presentation and conclusion drawing. The results showed that the Implementation of Village Index Development Policy in Kutawaringin District, Bandung Regency was assessed based on factors that influenced the implementation of policies, namely communication, resources, disposition and bureaucratic structure were not optimal. Obstacles in the Implementation of Village Index Development Policy in Kutawaringin District, Bandung Regency is the socialization that is less thorough, less clear and less intensive. Human resources, especially at the village level, do not understand SOP. Many villages do not want to join the policy program. There are still village chiefs who do not want their villages to rise because of concerns about not getting village development funding, and the dominant authority of village chiefs in some villages is less support in policy implementation. Efforts made to overcome obstacles are managing by continuing to conduct effective communication between all levels of bureaucracy/implementor policies ranging from the Bandung Regency level to the village level in the Kutawaringin District. Socialization and coaching continues to be carried out to villages, especially six villages that are still in developing village status. Providing more intensive motivation to villages that are already in Advanced Village status in order to try to increase into Independent Villages.